Evaluation of Groundwater Quality in People's Victory Canal Irrigation Area - LIU Zhongpei; CAI Qingfeng; DOU Ming; CHEN Ying (Renmin Zhujiang)
Groundwater quality evaluation is of great significance for knowing water quality and protecting water resources. Based on the monitoring results of 22 main monitoring wells in People’s Victory Canal Irrigation Area in 2016, this paper evaluates the groundwater quality in the study area by single factor evaluation method, Nemerow index method and fuzzy-entropy method, then compares & analyzes the evaluation results. The results show that the pollution in the monitoring point G04, G05, G14 and G15 is the most serious, and the more serious pollution factors are total hardness, total soluble solids, nitrite, etc. Groundwater quality is poor in both dry and wet seasons. However, from wet season to wet season, the quality of groundwater gets better due to the improvement of evaluation factors such as oxygen consumption, nitrite and ammonia nitrogen.